Male breast cancer and mantle cell lymphoma in a single patient: A case report and literature review. Issue 48 (December 2017) - Liu, Jun; Wei, Hongquan; Zhu, Keqing; Lai, Liqin; Han, Xiaoyu; Yang, Yue
Absract: Rationale: Although still relatively rare, multiple primary malignant neoplasms (MPMNs) have been increasingly reported in recent years. Patient concerns and diagnoses: A 65-year-old man was referred to our hospital for a painless, incidental left axillary lump. Ultrasound showed enlarged left axillary lymph nodes. An excisional biopsy was conducted on 3 lymph nodes. The pathological diagnosis was determined to be metastatic adenocarcinoma and mantle cell lymphoma (MCL) in the lymph nodes. Further physical examination of the patient yielded a 1.5-cm hard, left subareolar mass. Interventions and outcomes: The patient underwent modified radical mastectomy. The diagnosis was grade II invasive ductal carcinoma (stage IIA). The axillary lymph node showed MCL (stage I, group A), but not metastatic ductal carcinoma. The patient received chemotherapy, including 6 courses of CHOP (A chemotherapy protocol consists of cyclophosphamide 1.2 g day 1, doxorubicin 80 mg day 1, vindesine 4 mg day1, and prednisone 90 mg from day 1 to 5) for lymphoma and breast cancer. The patient was also administered endocrine therapy. After a 54-month follow-up, the patient was well with no evidence of disease. Lessons: MPMNs are easily misdiagnosed as a primary and metastatic tumor, leading to delayed or erroneous treatment. Male breast cancer in a patient with MCL is rare. Early diagnosis and proper therapy are necessary for an optimal prognosis. Further studies are required to define the mechanisms and risk factors of MPMNs.